Cost-effectiveness analysis of operative versus non-operative management of colorectal cancer metastases in the Finnish RAXO Study - Kontiainen, Joel; Lehtomäki, Kaisa; Muhonen, Timo; Hahl, Jarmo; Toppila, Iiro; Poussa, Tuija; Osterlund, Emerik; Heervä, Eetu; Stedt, Hanna; Kallio, Raija; Halonen, Päivi; Nordin, Arno; et al. (Medical Journals Sweden, 2026)
Background and purpose
Cancer therapies place an increasing financial burden on societies. In metastatic colorectal cancer (mCRC), an optimised curative-intent treatment combines metastasectomy, local ablative therapy, and perioperative systemic anti-cancer therapy (SACT) under multidisciplinary team guidance. The resource-intensive operative treatment strategy results in better survival than a non-operative approach with SACT only. The cost-effectiveness of the strategy including operative treatment has not been investigated in the era of modern treatment options.
Patient/material and methods
A Markov model was developed to estimate lifetime healthcare costs and quality-adjusted life-years (QALYs). Patients receiving operative treatment, including metastasectomy along with SACT, and those receiving non-operative treatment with SACT only, were identified from the prospective Finnish RAXO study that recruited 1,086 patients between 2012 and 2018. Cost-effectiveness analyses and sensitivity analyses were conducted from the healthcare payer’s perspective using 2023 cost levels.
Results
The mean lifetime costs (158,309€) for patients with an operative treatment produced 6.57 life years and 5.91 QALYs according to the Markov model. The non-operative treatment group had costs of 77,182€, producing 1.99 life years and 1.74 QALYs. The incremental cost-effectiveness ratio (ICER) was 19,455€/QALY, with the caveat that more favourable characteristics were present in the operative group. In probabilistic sensitivity analyses with a willingness-to-pay threshold of 30,000€/QALY, the operative treatment group had an 81% probability of being cost-effective. The results were robust in adjusted sensitivity analyses, including propensity score matched subgroups.
Interpretation
An operative treatment strategy is cost-effective at a commonly referenced acceptability threshold.